Thickening of spine ligamentum flavum and facet tropism - Appolonio,Paulo Roberto (2014)
OBJECTIVE: This study investigated the thickening of the ligamentum flavum (LF) and its correlation with facet tropism and its severity at different levels of the spine. METHOD: This retrospective study was performed with patients with chronic back pain consecutively admitted to a specialized spinal surgery service between January 2012 and January 2013. All patients underwent magnetic resonance imaging (MRI) to measure the thickness of the LF and facet tropism severity (severe, moderate or absent) according to the spine levels (L3 -L4, L4-L5, L5-S1). The association between the thickness of LF and facet tropism was analyzed. RESULTS: During the study period, 98 consecutive patients were enrolled with a mean age of 53.6 years, most women (59.2%). There was no significant difference between the thicknesses of the ligament and the presence of tropism in different spinal levels (p > 0.05). The thickness of LF was significantly associated with the severity of tropism only in L5-S1 level (p < 0.03). CONCLUSIONS: Our results show that there is a positive relationship between severe facet tropism and increased thickness of the LF in the L5-S1 level.